TAMAN NASIONAL WASUR, MENGELOLA KAWASAN KONSERVASI DI WILAYAH MASYARAKAT ADAT - Kosmaryandi, Nandi (Media Konservasi, 2016)
Indonesia has established 50 national parks as part of its protectedarea. Considerations ofthe establishment of national parks by the government were based on the conditions of native ecosystems and biodiversity conservation targets. Consideration was also as sociated with the development of recommendations made in the IUCN's World Park Congresses. It is a fact that some national parks were occupying some indigenous lands, such as Wasur National Park which occupied indigenous territories of Kanum, Marind-Kondo, Marori Men-gey and Yeinan Ethnics. These indigenous peoples have established natural resource management systems that were intimately associated with their traditions and beliefs. Discrepancy between government policies on conservation are as with the pattern of arrangement on indigenous peoples as owners of the area led to the emergence of conflict and marginalization of indigenous peoples’ rights. Realizing the error in the perspective of conservation area management related to indigenous peoples, in the 5th World Park Congress in Durban, South Africa in 200, a recommendation  was agreed on the importance of collaboration in the equality and mutual benefit between parks’ managers with indigenous peoples, and positioning indigenous peoples' rightsasan important part in conservation area management system today and the future. Keywords: national parks, indigenous peoples, wasur